2021
DOI: 10.1080/21655979.2021.2005876
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and in-silico findings reveal medical features and pharmacological targets of biochanin A against colorectal cancer and COVID-19

Abstract: Severe mortality due to the COVID-19 pandemic resulted from the lack of effective treatment. Although COVID-19 vaccines are available, their side effects have become a challenge for clinical use in patients with chronic diseases, especially cancer patients. In the current report, we applied network pharmacology and systematic bioinformatics to explore the use of biochanin A in patients with colorectal cancer (CRC) and COVID-19 infection. Using the network pharmacology approach, we identified two clusters of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Already, different phytochemicals, including curcumin (Jerah et al, 2015), formononetin (Suryani, 2018), and hesperetin (Jaganathan et al, 2021) have been evaluated for anticancer activities by computational approaches. Qin et al (2021) cells in breast cancer (Ren et al, 2018). According to an in silico study, and athymic mice at 50 μg/mL dose (Rice et al, 2002).…”
Section: In Silico Anticancer Activity Of Bcamentioning
confidence: 99%
See 3 more Smart Citations
“…Already, different phytochemicals, including curcumin (Jerah et al, 2015), formononetin (Suryani, 2018), and hesperetin (Jaganathan et al, 2021) have been evaluated for anticancer activities by computational approaches. Qin et al (2021) cells in breast cancer (Ren et al, 2018). According to an in silico study, and athymic mice at 50 μg/mL dose (Rice et al, 2002).…”
Section: In Silico Anticancer Activity Of Bcamentioning
confidence: 99%
“…Already, different phytochemicals, including curcumin (Jerah et al, 2015), formononetin (Suryani, 2018), and hesperetin (Jaganathan et al, 2021) have been evaluated for anticancer activities by computational approaches. Qin et al (2021) reported that BCA decreased cytokine production, including interleukin‐6, and controlled PI3K‐Akt and JAK‐STAT signaling mechanism, leading to regulating cell proliferation, cell growth, and apoptosis in COVID‐19‐infected CRC patients. Ghani et al (2020) invested with these compounds and found that BCA demonstrated a higher tendency for binding Bcl‐xl, particularly Bcl‐2 proteins, which had a binding energy of −8.5 kcal/mol, indicating inhibited apoptosis pathways in ovarian cancer.…”
Section: Anticancer Perspectives Of Bcamentioning
confidence: 99%
See 2 more Smart Citations
“…Some peptides and some drugs were recently identified through in silico experiments as potential candidates to treat COVID-19 disease ( Wang, 2020 ; Çakır et al, 2021 ; Qin et al, 2021 ). Wang (2020) was the first study to identify approved drugs that could be effective against the SARS-Cov-2, such as Lopinavir and Elbasvir.…”
Section: Therapeutic Potentials Of Avps Against Sars-cov-2mentioning
confidence: 99%